Use the properties of exponents to rewrite the expression.
(-3yz)(-3yz)(-3yz)(-3yz)
1 answer:
Answer:
Answer is 81y^4z^4
Step-by-step explanation:
The expression is (-3yz) (-3yz) (-3yz) (-3yz).
Since all the four terms have power 1:
(-3yz)^1 (-3yz)^1 (-3yz)^1 (-3yz)^1
We know that we can add the powers if the terms have same base
So,
=(-3yz)^1+1+1+1
=(-3yz)^4
=(-3)^4(y)^4(z)^4.
If the power is an even number than the negative sign changes into positive sign.
=3^4y^4z^4
=81y^4z^4
Thus the answer is 81y^4z^4....
You might be interested in
Answer:
0
Step-by-step explanation:
because your making it all to the zero power which equals zero
<span>Multiply both sides of the fraction
by 3.
3/4 = 9/12 </span>
Answer:
55,050
Step-by-step explanation: